The Prevalence of Malaria among Pregnant Women in Ethiopia: A Systematic Review and Meta-Analysis - Yalewayker Tegegne; Daniel Asmelash; Sintayehu Ambachew; Setegn Eshetie; Ayenew Addisu; Ayalew Jejaw Zeleke (Journal of Parasitology Research)
Background. Malaria during pregnancy remains a major public health concern in tropical and subtropical countries. Moreover, malaria is increasingly associated with unwanted pregnancy outcomes such as an increased risk of abortion, stillbirth, premature delivery, and low-birthweight infants. Since pregnant women are most vulnerable to malaria, implementation of the appropriate prevention and control measures among this group is very important. Therefore, the current review was designed to assess the prevalence of both symptomatic and asymptomatic malaria among pregnant women in Ethiopia. Method. In this systematic review and meta-analysis we have followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. The databases used were PubMed, Google Scholar, HINARI, and Science Direct literature. Search terms used were “prevalence”, “malaria”, “pregnant women”, and “Ethiopia”. Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI) was used for critical appraisal of studies. The meta-analysis was conducted using STATA 14 software. The pooled meta-logistic regression was computed to present the pooled prevalence with a 95% confidence interval (CI). Result. Among a total of 10207 studies, seven studies were included in this analysis. The estimated pooled prevalence of malaria among pregnant women in Ethiopia was 12.72% (95% CI: 7.45, 17.98). In subgroup analysis, the prevalence of malaria showed a significant variation between asymptomatic and symptomatic cases, which was 7.83% (95% CI: 2.23, 13.43) and 17.97% (95% CI: 7.31, 28.92), respectively. Conclusion. The current systematic review and meta-analysis showed that the pooled prevalence of malaria among pregnant women was found to be relatively higher compared with the general population. Therefore, the existing prevention and control measures should be strengthen.